Relationship Between Pitx2 Snps with Weights and Body Measurements in Goat: Hubungan Antara Pitx2 Snps dengan Bobot dan Ukuran Tubuh pada Kambing - Al-Rubaye, Shaimaa G. A.; Al-Zubaidi , Zainab Hussein Kareem; Redha , Huda Muhanna Redha; Kalaf, Ali Ahmed (Indonesian Journal on Health Science and Medicine, 2025)
This study was conducted at the Ruminant Research Station, affiliated with the Ministry of Agriculture, from December 1, 2021, to March 5, 2022. The objective was to investigate the relationship between single nucleotide polymorphisms (SNPs) in the Paired-like homeodomain transcription factor A (PITX1) gene and growth traits, including body measurements, in goats. A total of 52 female goats were used, including 16 native and 36 Shami goats. DNA sequencing of a 966 bp fragment from the promoter region of the PITX1 gene revealed four mutations. The SNPs G1198A and G1089A exhibited two genotypes: wild-type GG and heterozygous GA, with the mutant homozygous genotype AA not detected. For the C1194T SNP (referred to in the original text as ClYIT), three genotypes were identified: CC (wild), CT (heterozygous), and TT (mutant). Another SNP, G1003A, presented all three genotypes: GG, GA, and AA. The results showed that birth weight and body measurements, such as heart girth and body length, were significantly affected by the C1194T mutation and varied among genotypes. Most other growth traits, however, were not significantly influenced by breed differences. In detail, the highest dam birth weight was observed in the CC genotype (3.23 kg), while the CT genotype was associated with lower neonate birth weight (3.19 kg). The TT genotype (mutant) recorded the highest values for heart girth (83.4 cm) and body length (79.45 cm) in neonates. Furthermore, the G1003A mutation significantly increased dam birth weight, reaching 3.55 kg in individuals with the mutant AA genotype, although it had no significant effect on other growth traits or body dimensions. Highlights: PITX1 SNPs identified: Four mutations were found in the promoter region, notably C1194T and G1003A. Growth traits affected: C1194T and G1003A SNPs significantly influenced birth weight and body measurements. Genotype impact varies: TT and AA genotypes showed superior values in specific growth traits. Keywords: Pitx2, Goat, Snps, Growth, Traits